CORRELATION AND PATH ANALYSIS IN ORIENTAL PICKLING MELON (Cucumis melo L. var. conomon) GENOTYPES - R.V.S.K. REDDY, R. RAMESH BABU, N. HARIPRASAD RAO and (The Journal of Research, PJTSAU, 2017)
Correlation and path analysis was carried out for yield and yield attributing traits in 46 oriental pickling melon genotypes. Yield per vine was correlated positively and significantly with node number of first female flower, days to first female flower, fruit weight, fruit length, fruit girth, flesh thickness, placenta weight per fruit, days to first fruit harvest, seed cavity width, seed cavity length, TSS, number of fruits per vine, number of primary branches per vine and 100 seed weight. Path coefficient analysis revealed that traits like 100 seed weight, placenta weight per fruit and fruit weight exhibited high positive direct effect on fruit yield per vine and these traits recorded significant positive correlation with fruit yield per vine signifying the importance of these traits in selection programme for crop improvement.